Lithuanian Police Battalions in Pskov Region and in Kuršas: the 13th and 10(256)th (1942–1945) - Bubnys, Arūnas (Genocidas ir rezistencija, 2001)
This article tries to recreate history and activity of two police batalions 13th and 10th (256) in Pskov region and Kuršas: how they were created, what tasks they got.